PEMILIHAN SUPPLIER OBAT MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) DI BPM X - Muhammad Hafidz Yusuf; Muhammad Ajir Muzakki; Narto Narto (UPN Veteran Jawa Timur, 2020)
BPM X is Bidan Praktek Mandiri or Independent Practice Midwife that focuses on the maternal health services, female reproduction services, child health services, and family planning services. BPM X (Independence Practice Midwife) gets medicines from several suppliers. By the presence of several suppliers, BPM X gets the problematic case in determining the right supplier. To choose the right supplier, we need the right method for making the right decisions. The appropriate method to determine the right supplier uses Simple Additive Weighting (SAW). The data which is processed in the form of quality data, price data, service data, warranty. Assessment can be obtained by criteria wich will be used as a basis for rank existing suppliers. Assessment with each criterion is obtained from direct assessment by the owner of BPM X. By the selection of suppliers is expected to make the easier way for BPM X to compare the performance of suppliers. The results of this study uses the SAW method wich are able to get the right supplier. In the case to make decision in determining suppliers can help BPM X for evaluating suppliers.